Odontogenic cysts, tumors & fibro-osseseous lesions in children & adolescents: a pictorial essay - Abd. Aziz, Azian; Jesu, Vincent C.; Yogeswari, S. (2009)
Maxillomandibular lesions including the odontogenic tumors that affect children and adolescent are most frequently benign. A complete clinical history, thorough physical examination radiological findings may narrow down the differential diagnosis. However these lesions may appear almost similar radiologically making accurate single diagnosis based on imaging alone difficult. Surgical excision, resection and histological diagnosis are most often indicated.